2016
DOI: 10.1007/s10803-016-2859-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parenting Styles Fail to Mediate Between Anxiety and Attachment Styles in Adult Siblings of Individuals with Developmental Disabilities

Abstract: Adult siblings of individuals with developmental disabilities often experience higher levels of anxiety than individuals in the general population. The present study tested whether perceived parenting could mediate the relationship between attachment styles and anxiety in the sibling group compared to a control group. Little association was found between perceived parenting and attachment styles or anxiety for the siblings but there were robust and expected findings for the control. Adult attachment-related-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…However, in empirical investigations of the links between adult attachment orientations and mental health, there is substantial variance in the magnitude of reported associations. For example, many studies have found that attachment anxiety is highly correlated with generalized anxiety (e.g., r s ≥ .47; Bekker & Croon, 2010; English et al, 2018; O’Neill & Murray, 2016). In contrast, other studies have reported a more moderate correlation between attachment anxiety and generalized anxiety (e.g., r ≤ .24; Kidd et al, 2016; Meredith et al, 2016; Ng & Hou, 2017; Patel, 2008).…”
Section: Adult Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in empirical investigations of the links between adult attachment orientations and mental health, there is substantial variance in the magnitude of reported associations. For example, many studies have found that attachment anxiety is highly correlated with generalized anxiety (e.g., r s ≥ .47; Bekker & Croon, 2010; English et al, 2018; O’Neill & Murray, 2016). In contrast, other studies have reported a more moderate correlation between attachment anxiety and generalized anxiety (e.g., r ≤ .24; Kidd et al, 2016; Meredith et al, 2016; Ng & Hou, 2017; Patel, 2008).…”
Section: Adult Attachmentmentioning
confidence: 99%
“…Thus, we examined whether relationship status moderated the correlation between adult attachment and mental health. That said, cohabitation with an unmarried romantic partner and marriage may have similar psychological effects, and many studies tend to report the proportion of married or cohabiting participants in total (Dagnino et al, 2017; Espeleta et al, 2017; Falgares et al, 2019; Kohlhoff & Barnett, 2013; Marques et al, 2018; Nielsen et al, 2017; O’Neill & Murray, 2016; Reizer, 2015; Segel-Karpas et al, 2013; Zech et al, 2006). Thus, we operationalized relationship status as cohabiting and/or married versus not.…”
Section: Adult Attachmentmentioning
confidence: 99%
“…In addition, the conclusions aligned with the study, which found that in Spain, parents felt responsible for the happiness of their children and developed an overprotective approach towards their care [ 52 ]. Comparably, a caretaking attachment bond mainly develops between the child and caregiver based on love, interaction, and the child’s feeling more uncomfortable in the caregiver’s absence [ 53 ]. Hence, the overprotectiveness of children with ID sometimes makes it difficult for caregivers to combine their work life and the care of their children with ID [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…O ile kwestia więzi i jej uwarunkowań we wcześniejszych latach została w pewnym stopniu zweryfikowana badawczo (Buhrmester, Furman, 1990;Buist, Deković, Prinzie, 2013;Campione-Barr, Smetana, 2010;Cruise, O'Reilly, 2014;Dunn, 1988;Faith, Elledge, Newgent, Cavell, 2015;Kitzman, Cohen, Lockwood, 2002;Stocker i in., 2002), tak późniejsze lata były do tej pory dość rzadko obiektem zainteresowania. Większość najnowszych badań dotyczących dorosłego życia rodzeństw odnosi się do sytuacji wyjątkowych, w których jedno z rodzeństwa jest niepełnosprawne fizycznie, intelektualnie bądź cierpi na zaburzenia psychicznie (Burbidge, Minnes, 2014;Burke, Lee, Arnold, Owen, 2017;Cuskelly, 2016;Ewertzon, Cronqvist, Lützén, Andershed, 2012;Hall, Rossetti, 2017;Hallion, Taylor, Roberts, 2018;Horwitz, 1993;Howlin, Moss, Savage, Bolton, Rutter, 2015;O'Neill, Murray, 2016;Rossetti, Hall, 2015;Tomeny, Ellis, Rankin, Barry, 2017). Znacznie mniej jest natomiast badań dotyczących funkcjonowania zdrowych braci i sióstr (Jensen, Whiteman, Rand, Fingerman, 2017;Mikkelson, Myers, Hannawa, 2011;Ngangana, Davis, Burns, McGee, Montgomery, 2016;Walęcka-Matyja, 2015).…”
Section: Relacja Między Rodzeństwem W Dorosłości -Przegląd Zagadnieńunclassified